2018
DOI: 10.1093/gigascience/giy105
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide definition of selective sweeps reveals molecular evidence of trait-driven domestication among elite goat (Capra species) breeds for the production of dairy, cashmere, and meat

Abstract: BackgroundThe domestication of wild goats and subsequent intensive trait-driven crossing, inbreeding, and selection have led to dramatic phenotypic purification and intermediate breeds for the high-quality production of dairy, cashmere wool, and meat. Genomic resequencing provides a powerful means for the direct identification of trait-associated sequence variations that underlie molecular mechanisms of domestication.ResultsHere, we report our effort to define such variations based on data from domestic goat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
1
27
1
1
Order By: Relevance
“…For instance, the causal factor of the white color typical of many sheep breeds is the ubiquitous expression of a duplicated copy of the ASIP coding sequence, which is regulated by a duplicated promoter corresponding to the itchy E3 ubiquitin protein ligase gene [6,39]. Although some studies proposed that the ASIP CNV might be associated with different pigmentation patterns in goats [8,17,37], no functional assay has verified an association of ASIP copy number with ASIP mRNA levels. Another interesting shared copy number variable gene is ADAMTS20, which was also identified in two previous CNV surveys [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the causal factor of the white color typical of many sheep breeds is the ubiquitous expression of a duplicated copy of the ASIP coding sequence, which is regulated by a duplicated promoter corresponding to the itchy E3 ubiquitin protein ligase gene [6,39]. Although some studies proposed that the ASIP CNV might be associated with different pigmentation patterns in goats [8,17,37], no functional assay has verified an association of ASIP copy number with ASIP mRNA levels. Another interesting shared copy number variable gene is ADAMTS20, which was also identified in two previous CNV surveys [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons for addressing these associations. First, a region on chromosome 3 was reported to show the highest intensity signal effect on meat traits in goats, which includes the HIAT1, SLC35A3, and SASS6 genes [19,21]. The same region spanning 43.3 to 43.8 Mb on chromosome 3 of water buffalo was shown to affect milk fat and protein percentages, and this region harbors the HIAT1, SLC35A3, and PALMD genes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The HIAT1 gene, which is also known as MFSD14A (major facilitator superfamily domain containing 14A), plays a role in transmembrane transport and the molecular function of transporter activity [18]. Our previous genome resequencing study of goats revealed that a set of genes play critical roles in meat goats compared with wool and dairy breeds, including the HIAT1 gene [19]. In addition, HIAT1 was identified as a novel candidate gene for milk production in buffaloes and was localized to a bovine QTL (quantitative trait locus) affecting the milk fat yield and protein yield [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the growth hormone (GH) gene influences the expression of growth and milk characteristics. The vital candidate genes for goat play a significant role in the production, reproduction, metabolism, sex determination, and disease resistance [4,[12][13][14][15][16]. A study of the candidate genes for major economic traits could be applied for a direct search of QTL in terms of planning future breeding program.…”
Section: Introductionmentioning
confidence: 99%